Answer:
3.
a=-1
a=-2
5.
n=-6
n=-3
8.
n=-5
n=-3
Explanation:
3. separate into probable cases
![a + 2 = 0\\ a + 1 = 0](https://img.qammunity.org/2022/formulas/mathematics/college/evr9dnvq22o9s320c0ja6q8qpj3of5w171.png)
5.
![{n}^(2) + 6n - 3n - 18 = 0 \\](https://img.qammunity.org/2022/formulas/mathematics/college/fcweqtczumxwmvne06b59y1snprhw5r7c8.png)
factor out n from the expression
factor out -3 from the expression
![n * (n + 6) - 3(n + 6) = 0](https://img.qammunity.org/2022/formulas/mathematics/college/obhyw2tpfq3tj6qlmudbzygk2n6poeg1of.png)
factor out n+6 from the equation
![(n + 6) * (n - 3) = 0](https://img.qammunity.org/2022/formulas/mathematics/college/5cufo93r6a9wkr34kx9bvqwq6maugidm5j.png)
separate into probable cases
![n + 6 = 0\\ n - 3 = 0](https://img.qammunity.org/2022/formulas/mathematics/college/q2q1okkcp51e8z97muktw0cjrrqxvpbbdd.png)
solve the equations
![n = - 6 \\ n = 3](https://img.qammunity.org/2022/formulas/mathematics/college/ft733suf1s5h7sf4dcs57x5nb1te3rwmih.png)
8.
![n ^(2) + 5n + 3n + 15 = 0](https://img.qammunity.org/2022/formulas/mathematics/college/jo86bkaojisn9bbwcnzw9312g056ultvv4.png)
factor out n and 3 from the expression
![n * (n + 5) + 3(n + 5) = 0](https://img.qammunity.org/2022/formulas/mathematics/college/nslg8crus1xeo5ei3hpqbulrr5zpgtbgws.png)
factor out n+5
![(n + 5) * (n + 3) = 0](https://img.qammunity.org/2022/formulas/mathematics/college/25ulm6ebpvukxsre4henoanhh3r84agzur.png)
separate into probable cases
![n + 5 = 0 \\ n + 3 = 0](https://img.qammunity.org/2022/formulas/mathematics/college/zqkzab7ujwyy84od6cn4zdte7xjis1xp6l.png)
solve the equations
![n = - 3 \\ n = - 3](https://img.qammunity.org/2022/formulas/mathematics/college/ktlz85jqjununi792ac7q2gvzf0a7eijbx.png)